Gaya Kepemimpinan, Motivasi Dosen, dan Model Pentahelix dalam Mendukung Implementasi Kurikulum Merdeka Belajar Kampus Merdeka (Studi di Universitas Muhammadiyah Sidoarjo) - Dessy Kartika Yudityawati; Sigit Hermawan (SENTRALISASI, 2023)
The principle of ‘Merdeka Belajar’ is expected to accelerate the process of education reform in Indonesia. Rigid, linear, and bureaucratic education is not suitable for an era where technology is developing rapidly. Curriculum that is responsive to the times, adaptive and innovative is the answer. The purpose of the study is to determine the role of leadership style, lecturer motivation, and the pentahelix model in supporting the implementation of Merdeka Belajar Kampus Merdeka’s Curriculum at Universitas Muhammadiyah Sidoarjo. The research falls into the category of qualitative research with an interpretive paradigm, and uses several data collection techniques, including interviews, observation, and documentation. The results showed that leadership style, lecturer motivation, and the pentahelix model played a role in the implementation of MBKM at Universitas Muhammadiyah Sidoarjo. The 'TORSIE' paradigm and transformational leadership style bring Universitas Muhammadiyah Sidoarjo towards dynamic and quality education. The motivation of the lecturers is primarily in the context of self-development, making MBKM not just learning outside the Study Program, but internalizing MBKM to the creation of collaborative, innovative and participatory classes. The Pentahelix model, integration between the Government, academia, business, media, and society, as a manifestation of collaboration and synergy between Muhammadiyah University of Sidoarjo and other institutions completes it all. In the scientific field, it is hoped that the results of this study will be used as a reference for further research.